Johan Huizinga and the concept of playfulness: contribution of Philosophy to Mathematics children's literature - Claudionor Renato Da Silva (Pontificia Universidad Católica del Perú, 2018)
Homo Ludens, a work written by Johan Huizinga is another alternative for the conceptualization and use of the term ludic in mathematical education, with a significant contribution to the pedagogical practice involving children's mathematical literature or children's literature with mathematical content, replacing the recurrent use of the terms »play» and »playful» from the field of educational psychology. From the bibliographic method, the study allowed three general conclusions: the first is the presence of philosophy in mathematics education with the use of children's literature; the second, arising from the first is the possibility of philosophy to enter the contents of mathematics by encouraging logical reasoning, from early childhood education; and, lastly, that there are many gains in teacher training, in pedagogy courses, especially in the promotion of learning and knowledge in mathematical education, under the play, which are part of a philosophically based perspective present in the work Homo Ludens of the Huizinga.